2020
DOI: 10.1021/acs.jpcc.0c06652
|View full text |Cite
|
Sign up to set email alerts
|

Surface Evolution of Cu–Ag Bimetallic Systems: From Experiments to Molecular Dynamics Simulation

Abstract: In this article, we prepare corncob-like Cu–Ag and core–shell Cu@Ag bimetallic structures by controlling the concentration of Ag and Cu salts via a galvanic replacement reaction. Moreover, the structure evolution and electrical resistivity of the Cu–Ag corncob nanoparticle deposits were investigated upon heating up to 260 °C by experiments. Afterward, the effect of the distinctiveness and arrangement (such as core@shell, bifacial Janus, and nanowire structure) on the sintering behavior of Cu–Ag systems was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Liang et al investigated the structural evolution of various Cu-Ag nanoparticles by using molecular dynamics (MD) simulation, and found that the surface morphology and structure changed significantly at different temperatures. 39 Monte Carlo simulation was used to calculate the segregation isotherms and determine the segregation equilibrium of the Ag/Cu(111) surface. 40 Herein, we further investigated the segregation process of Cu-Ag bimetallic nanoparticles (NPs) before and after CO adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al investigated the structural evolution of various Cu-Ag nanoparticles by using molecular dynamics (MD) simulation, and found that the surface morphology and structure changed significantly at different temperatures. 39 Monte Carlo simulation was used to calculate the segregation isotherms and determine the segregation equilibrium of the Ag/Cu(111) surface. 40 Herein, we further investigated the segregation process of Cu-Ag bimetallic nanoparticles (NPs) before and after CO adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic nanostructure-based plasmonic systems have a significant advantage over their monometallic counterparts due to the spectral tunability of the localized plasmon resonances arising from the compositional difference. Herein, we investigate the strong plasmon-exciton coupling interactions of bimetallic gold-silver core-shell NRs with the J -aggregate of the cationic cyanine dye, 1,1′-diethyl-2,2′-cyanine iodide (Cy). The nanostructure with Au NRs as the core and silver as the shell (hereafter referred as Au@Ag NRs) is employed as an effective plasmonic material where the Ag shell thickness is used as the parameter for fine-tuning the plasmon resonance to establish a perfect resonance with the excitonic counterparts. , The ensemble-level plasmon-exciton coupling is monitored using UV–vis absorption spectroscopy, whereas DFM is adopted to monitor these interactions at the single-particle level.…”
Section: Introductionmentioning
confidence: 99%
“…22−24 However, there are rare experimental investigations on the self-assembly dynamics process of BJNPs. 25 In addition, molecular dynamics (MD) simulations are mainly focused on exploring the stability, 26 formation, 27,28 and melting behavior 29 of BJNPs. A physical picture that captures the detailed mechanisms of BJNP selfassembly, which is crucial for precise control in metamaterial synthesis, remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembly of NPs provides a simple and powerful way to achieve ordered and well-defined nanoarchitecture. These complex NP superstructures with unique and enhanced properties can satisfy advanced technological requirements, such as photovoltaics, energy, and storage devices. , The excellent physicochemical properties of BJNPs make them ideal building blocks self-assembled to form functional nanoarchitecture. However, there are rare experimental investigations on the self-assembly dynamics process of BJNPs . In addition, molecular dynamics (MD) simulations are mainly focused on exploring the stability, formation, , and melting behavior of BJNPs. A physical picture that captures the detailed mechanisms of BJNP self-assembly, which is crucial for precise control in metamaterial synthesis, remains elusive.…”
Section: Introductionmentioning
confidence: 99%